logo for solving-math-problems.com
leftimage for solving-math-problems.com

3z(x⁹y⁷)^(4/5), simplify radicals

by Gretchen
(York)











































Write each answer using only positive exponents.
1. (27a^3b^-6)(a^-1/3b^5/6c^2/3)^6

2.(x^1/2y^-3/4 / y^2/3)

3.Evaluate (-64)^2/3

4.Evaluate (4)^-5/2

5. Express 3z(x^9y^7)^4/5

Comments for 3z(x⁹y⁷)^(4/5), simplify radicals

Click here to add your own comments

Apr 14, 2011
Radicals
by: Staff


The question:

by Gretchen
(York)

Write each answer using only positive exponents.

1.(27a^3b^-6)(a^-1/3b^5/6c^2/3)^6

2.(x^1/2y^-3/4 / y^2/3)

3.Evaluate (-64)^2/3

4.Evaluate (4)^-5/2

5. Express 3z(x^9y^7)^4/5


The answer:

1. (27a^3b^-6)(a^-1/3b^5/6c^2/3)^6

Click the following link to see how the expression can be simplified (use the Backspace key to return to this page)

http://www.solving-math-problems.com/images/radicals-simplify-expression1.png


2. (x^1/2y^-3/4 / y^2/3)

(x^(1/2))y^(-3/4) / y^(2/3)

Click the following link to see how the expression can be simplified (use the Backspace key to return to this page)

http://www.solving-math-problems.com/images/radicals-simplify-expression2.png


3.Evaluate (-64)^2/3

= ∛(-64)²

= ∛(64)²

= ∛(8*8*8*8)

= ∛(8³*2³)

= 8*2

= 16

4.Evaluate (4)^-5/2

= √[(1/((4)^ 5)]

= √1/√((4)^ 5)

= 1/√((4)^ 5)

= 1/√(4²*4²*2²)

= 1/(4²*2)

= 1/(16*2)

= 1/32

5. Express 3z(x^9y^7)^4/5

= 3z((x^9)(y^7))^(4/5)

= 3z*(x^9)^(4/5)*(y^7))^(4/5)

= 3z*x^(36/5)*y^(28/5)




Thanks for writing.


Staff
www.solving-math-problems.com


Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com